ZERO WASTE PROGRAM TO SUPPORT SUSTAINABLE DEVELOPMENT GOALS (SDGS) IN URBAN AREAS - Wasis Riyanto; Nihayatus Sholichah; Ika Devy pramudiana (International Journal of Multidisciplinary Reseach, 2026)
Urban waste generation continues to rise along with population and consumption growth, while capacity management still relies on downstream handling so that waste reduction at the source remains suboptimal; this is the main problem underlying the study. This study aims to analyze the implementation of the zero waste program in Surabaya City and its contribution to achieving the Sustainable Development Goals (SDGs). A qualitative descriptive approach with a case study design was used. The population comprised waste management stakeholders in Surabaya City, with a sample of ten informants selected purposively, including environmental agency officials, field officers, 3R waste facility managers, waste bank administrators, environmental cadres, residents, business actors, collector partners, and academics. Data were collected through interviews, observation, and documentation, supplemented by 2024 secondary data, then analyzed using the Miles and Huberman interactive model through data reduction, data display, and conclusion drawing, and validated through triangulation. The results show that Surabaya manages approximately 99% of its waste, yet source reduction only reached 7.43% and residue at 3R facilities reached 47%, with a composition dominated by organic waste at 55.5%; community participation is the decisive factor for success. It is concluded that the zero waste program contributes to SDGs 11, 12, and 13, but its sustainability requires strengthening source separation, community education, and shifting the success indicator from the volume of waste handled toward the volume prevented, reused, and recycled